Pengaruh Budaya Organisasi, Kepemimpinan Transformasional, dan Disiplin Kerja terhadap Organizational Citizenship Behavior (OCB) (Studi pada PT. Derma Beauty Indonesia) - Kristin Yulia Setyowati; Kusuma Chandra Kirana; Didik Subiyanto (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine and examine the influence of organizational culture, transformational leadership, and work discipline on organizational citizenship behavior (OCB) at PT. Derma Beauty Indonesia. The population used in this study were employees of PT. Derma Beauty Indonesia with a total sample of 55 respondents. The sample used is saturated sampling, which means that all members of the population are sampled in this study. Data collection by using a questionnaire. The data analysis technique used is multiple linear regression analysis which aims to calculate the magnitude of the regression coefficient to show the magnitude of the influence of organizational culture, transformational leadership, and work discipline on organizational citizenship behavior (OCB). While the feasibility test of the model shows that the variables of organizational culture, transformational leadership, and work discipline together have a significant effect on organizational citizenship behavior (OCB) at PT. Derma Beauty Indonesia. The results of this study indicate that: (1) organizational culture has a significant effect on OCB; (2) transformational leadership has a significant effect on OCB; (3) work discipline has a significant effect on OCB; (4) organizational culture, transformational leadership, and work discipline have a significant effect against OCB.